Development of Learning Media for Children's Art Periodization for PGSD Students as a Strategy for Optimizing the Competencies of Future Educators (Indo-MathEdu Intellectuals Journal, 2025)
Primary education plays an important role in preparing the younger generation to face future challenges. In the context of art education, understanding the periodization of children's art is the key for educators in teaching art appropriately according to the stage of children's development. This research aims to develop learning media that can strengthen the understanding of prospective educators about the periodization of children's arts. This research uses a research and development (R&D) approach with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. Data analysis includes evaluations of the product assessment and learning outcomes. The data analysis process uses a descriptive quantitative method. The results of the study indicate that the developed learning media can improve students' understanding of children's art periodization. Prior to using the media, most students had not yet achieved learning mastery, but after using the media, 31 out of 32 students achieved mastery. Expert validation shows that the developed media and material are very feasible to use. Therefore, this learning media has proven effective in improving learning outcomes and understanding of children's art periodization